2022
DOI: 10.3389/fped.2021.728548
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Renal and Urinary Tract Anomalies Delineated by an Ultrasound Screening Program in Infants

Abstract: ObjectiveTo evaluate the value of ultrasound screening for congenital anomalies of the kidney and urinary tract (CAKUT) during the early postnatal period.MethodsThis is a prospective study that enrolled all neonates born from August 2019 to July 2020 at one medical center. Postnatal ultrasound screening was conducted in all neonates at 1, 3, and 6 months old, respectively. Information on antenatal detection and pregnancy was collected. We performed logistic regression analyses and established a predictive mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…In one study Bhat et al reported that low birth weight and preterm birth were significantly associated with genitourinary anomalies [29]. Similar findings were reported in other different studies [1,28]. Contrary to our findings where majority (67.0%) of the patients had normal birth weight during their delivery, and 86.2% of them were born at term, these factors were not statistically significant risk factor, hence warranting further studies in our setting to provide evidence.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In one study Bhat et al reported that low birth weight and preterm birth were significantly associated with genitourinary anomalies [29]. Similar findings were reported in other different studies [1,28]. Contrary to our findings where majority (67.0%) of the patients had normal birth weight during their delivery, and 86.2% of them were born at term, these factors were not statistically significant risk factor, hence warranting further studies in our setting to provide evidence.…”
Section: Discussionsupporting
confidence: 66%
“…Low birth weight and prematurity have been associated with severe morbidity and congenital anomalies including genito-urinary system [28]. In one study Bhat et al reported that low birth weight and preterm birth were significantly associated with genitourinary anomalies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies evaluated the risk factors associated with CAKUT. In one of those, Liu et al (7) reported that male gender, preterm birth, abnormal antenatal USG, gestational hypothyroidism, and oligohydramnios were associated with increased CAKUT risk during pregnancy. Our results partly supported these risk factors, which the majority of our cases were male, and all had abnormal antenatal urinary system USG findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent prospective study from China of 4,877 infants identified 268 cases (5.5%) of CAKUT by primary screening and 92 cases (1.9%) by tertiary screening. This study devised a predictive model incorporating high risk factors, namely male gender, preterm birth, antenatal abnormal ultrasound findings, gestational hypothyroidism, and oligohydramnios, all of which increase the risk of CAKUT (Liu et al, 2022).…”
Section: Screening For Cakutmentioning
confidence: 99%